Bone and Mineral Metabolism in Patients with Primary Aldosteronism. (3rd April 2014) - Petramala, Luigi; Zinnamosca, Laura; Settevendemmie, Amina; Marinelli, Cristiano; Nardi, Matteo; Concistrè, Antonio; Corpaci, Francesco; Tonnarini, Gianfranco; De Toma, Giorgio; Letizia, Claudio
Abstract : Primary aldosteronism represents major cause of secondary hypertension, strongly associated with high cardiovascular morbidity and mortality. Aldosterone excess may influence mineral homeostasis, through higher urinary calcium excretion inducing secondary increase of parathyroid hormone. Recently, in a cohort of PA patients a significant increase of primary hyperparathyroidism was found, suggesting a bidirectional functional link between the adrenal and parathyroid glands. The aim of this study was to evaluate the impact of aldosterone excess on mineral metabolism and bone mass density. In 73 PA patients we evaluated anthropometric and biochemical parameters, renin-angiotensin-aldosterone system, calcium-phosphorus metabolism, and bone mineral density; control groups were 73 essential hypertension (EH) subjects and 40 healthy subjects. Compared to HS and EH, PA subjects had significantly lower serum calcium levels and higher urinary calcium excretion. Moreover, PA patients showed higher plasma PTH, lower serum 25(OH)-vitamin D levels, higher prevalence of vitamin D deficiency (65% versus 25% and 25%; P < 0.001 ), and higher prevalence of osteopenia/osteoporosis (38.5 and 10.5%) than EH (28% and 4%) and NS (25% and 5%), respectively. This study supports the hypothesis that bone loss and fracture risk in PA patients are potentially the result of aldosterone mediated hypercalciuria and the consecutive secondary hyperparathyroidism.